2017
DOI: 10.1093/asj/sjx078
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Cells For Facial Surgery: Biofilling and Biocontouring

Abstract: Zuk et al in 2001 identified stem and regenerative cells within the stromal vascular fraction of fat. In preclinical studies, these cells appeared to stimulate angiogenesis and reduce inflammation, and soon thereafter, clinical use of stromal vascular fraction (SVF) evolved as researchers such as Rigotti, Coleman, Mojallal, our group, and others demonstrated that fat can be used for both therapeutic and aesthetic indications. The regenerative effects of fat and its contents on facial aesthetics have been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 32 publications
0
52
0
1
Order By: Relevance
“…In recent years, adipocyte-derived stem cells, platelet-rich plasma (PRP), and stromal vascular fraction (SVF) have been widely used for both therapeutic and esthetic indications because of their capacity for angiogenesis and wound healing. [39] Many studies have investigated the effects of cell-assisted fat grafting on increasing fat survival. Sasaki et al [21] reported a prospective study of 236 patients in 4 groups using conventional fat grafting, PRP-assisted fat grafting, SVF-assisted fat grafting, and PRP/SVF-assisted fat grafting.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, adipocyte-derived stem cells, platelet-rich plasma (PRP), and stromal vascular fraction (SVF) have been widely used for both therapeutic and esthetic indications because of their capacity for angiogenesis and wound healing. [39] Many studies have investigated the effects of cell-assisted fat grafting on increasing fat survival. Sasaki et al [21] reported a prospective study of 236 patients in 4 groups using conventional fat grafting, PRP-assisted fat grafting, SVF-assisted fat grafting, and PRP/SVF-assisted fat grafting.…”
Section: Discussionmentioning
confidence: 99%
“…The technique referred as “Injectable Tissue Replacement and Regeneration—ITR 2 ” is designed to replace and regenerate losses in deep and superficial fat compartments, bone, skin as well as in capillary density, elastin, and collagen tissues . Candidates for the procedure are patients having different types of facelifts who have associated volume loss and patients having laser therapies, where skin damage with thinning of the dermis and epithelium, fat, and bone loss has occurred.…”
Section: Enzyme‐free Methods Of Adipose Tissue Processingmentioning
confidence: 99%
“…For the problem of self-absorption, it may be necessary to perform another operation [ 81 ]. The clinical application of autologous fat is not only used for routine cosmetic treatment, such as wrinkle removal but also widely used for congenital defects, trauma, or reconstruction of surgically removed tissues, such as breast collapse after breast tumor surgery [ 82 ] and soft tissue deficiency after maxillofacial surgery [ 83 ].…”
Section: Classification Of Plastic Cosmetic Materialsmentioning
confidence: 99%